2018
DOI: 10.1021/acs.jpcb.8b08699
|View full text |Cite
|
Sign up to set email alerts
|

Distinctly Different Electroresponsive Electrorheological Effect in Low-Molecular-Weight and Polymerized Ionic Liquids: Rheological and Dielectric Relaxation Studies

Abstract: Owing to the robust and tunable properties compared to molecular compounds, ionic liquids (ILs) and polymeric ionic liquids (PILs) are very suitable substances to obtain available smart materials with high stability and strong stimulus-responsive characteristic. In this paper, electroresponsive smart electrorheological (ER) effects in low-molecular-weight and polymeric ionic liquids, such as poly­[[2-(methacryloyloxy)­ethyl]­trimethylammonium hexafluorophosphate] (P­[MTMA]­[PF6]) are investigated and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…First, three PILs were milled and sieved into particles of 5–15 μm. Then, the density of particles was measured via the method reported in our previous paper [ 12 ]. Simply, the particles were added into the pycnometer (5.0 mL) containing silicone oil and the pycnometer was placed in an ultrasonic cleaning bath and connected to a vacuum pump.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, three PILs were milled and sieved into particles of 5–15 μm. Then, the density of particles was measured via the method reported in our previous paper [ 12 ]. Simply, the particles were added into the pycnometer (5.0 mL) containing silicone oil and the pycnometer was placed in an ultrasonic cleaning bath and connected to a vacuum pump.…”
Section: Methodsmentioning
confidence: 99%
“…Different from conventional polyelectrolyte particles whose ER property needs to activate by absorbing moisture, the dry PIL particles have strong ER property. This is because, compared to the conventional polyelectrolytes, the ion-pair interaction in PIL particles is weaker due to large and delocalized nature of polyatomic fluorinated constituent ions and, thus, the untethered ions are easy to dissociate and move to induce interfacial polarization [ 12 ]. Furthermore, the hydrophobic nature of fluorinated constituent ions also makes PIL-based ERF to be insensitive to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Under the DC electric field, they found that composite particles with matching electrical properties had more stable ER properties. When the relaxation time of dispersed particles is in the range of 1.6 × 10 −3 –1.6 × 10 −6 s [ 24 , 100 , 101 , 102 ], the particles have an appropriate polarization rate. Under the combined action of electric field and shear field, the particles can produce a sufficient polarization rate and stable interaction force between particles.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…For ILs, the structures and properties of anion can affect the non-electrostatic interaction between ILs [ 123 ]. Among the anions of ILs, [TFSI] − is an hydrophobic one, whose large size and weak electrostatic interaction with cations lead to relatively large ion mobility and wide use in electrolytes [ 48 , 124 ]. Whereas it may be not the same in ER fluids.…”
Section: Er Responsesmentioning
confidence: 99%